Beliefs About Infant Regulation, Early Infant Behaviors and Maternal Postnatal Depressive Symptoms. Issue 2 (31st March 2014) - Muscat, Tracey; Obst, Patricia; Cockshaw, Wendell; Thorpe, Karen
Abstract Background Young infants may have irregular sleeping and feeding patterns. Such regulation difficulties are known correlates of maternal depressive symptoms. Parental beliefs about their role in regulating infant behaviors also may play a role. We investigated the association of depressive symptoms with infant feeding/sleeping behaviors, parent regulation beliefs, and the interaction of the two. Method In 2006, 272 mothers of infants aged up to 24 weeks completed a questionnaire about infant behavior and regulation beliefs. Participants were recruited from general medical practices and child health clinics in Brisbane, Australia. Depressive symptomology was measured using the Edinburgh Postnatal Depression Scale. Other measures were adapted from the ALSPAC study. Results Regression analyses were run controlling for partner support, other support, life events, and a range of demographic variables. Maternal depressive symptoms were associated with infant sleeping and feeding problems but not regulation beliefs. The most important infant predictor was sleep behaviors with feeding behaviors accounting for little additional variance. An interaction between regulation beliefs and sleep behaviors was found. Mothers with high regulation beliefs were more susceptible to postnatal depressive symptoms when infant sleep behaviors were problematic. Conclusion Mothers of young infants who expect greater control are more susceptible to depressive symptoms when their infant presents challenging sleep behavior.